Conocimientos, actitudes y prácticas sobre Papanicolaou en mujeres de edad fértil que acuden al Hospital Universitario de Motupe Loja - Minga Minga, Gibelly Celena (2020)
The Pap test is an exfoliative cytological sample of the cervix, used in screening for cervical cancer. Cervical cancer is very common; It ranks second among all malignant tumors in women both globally and nationally. The objective of this research was to assess the knowledge, attitudes and practices of the Pap smear in women of childbearing age attending the University Hospital of Motupe, Loja. This is a descriptive study, with a quantitative cross-sectional approach, developed at the University Hospital of Motupe Loja, from August 2018 to January 2019, with a population of 7753 patients, from which a sample of 366 women was taken. The results obtained were: more than fifty percent of respondents belonged to the age range of 18 to 33 years of age and women presented a level of knowledge in decreasing order: medium, low and high (with a percentage of 49.45%, 49.18% and 1.37% respectively). Most of the patients displayed negative attitudes (66.12%) with respect to the Pap smear, compared to positive attitudes (33.88%). Most of the respondents adopted incorrect practices (73.22%) versus the correct ones (26.78%). Finally, it was concluded that the level of knowledge was medium, attitudes were negative and practices were incorrect. Key words: exfoliative cytology, screening, cervical cancer, malignant tumors.